2014
DOI: 10.1590/0103-6440201302338
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effect and Transdentinal Diffusion of New Intracanal Formulations Containing Nitrofurantoin or Doxycycline

Abstract: The aim of this study was to investigate in vitro the antimicrobial effect and diffusion against E. faecalis of new intracanal medications on the external root surface. The medications tested were a placebo gel (PC); the new formulations with either 3% nitrofurantoin (NIT) or 3% doxycycline hydrochloride (DX) and 2% chlorhexidine (CHX) gel as positive control. The new formulations were tested using the traditional agar diffusion test (ADT) and an adapted agar diffusion method (AADM), where the teeth were fille… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
(21 reference statements)
1
7
1
2
Order By: Relevance
“…Un concepto interesante con respecto a la efectividad del medicamento dentro del conducto radicular, es la zona de inhibición, lo cual indicaría la actividad contra los microorganismos, su efectividad depende de varios factores, como el tamaño de la molécula, solubilidad y difusión del material en el medio de agar, sensibilidad a la droga, origen bacteriano, número de bacterias inoculadas, pH del sustrato, viscosidad del agar, tiempo de incubación y actividad metabólica en contra del microorganismo (Silva et al, 2014). Motivo por el cual, en el presente trabajo no se evalua la "zona de inhibición", por ser un concepto tan amplio.…”
Section: Discussionunclassified
“…Un concepto interesante con respecto a la efectividad del medicamento dentro del conducto radicular, es la zona de inhibición, lo cual indicaría la actividad contra los microorganismos, su efectividad depende de varios factores, como el tamaño de la molécula, solubilidad y difusión del material en el medio de agar, sensibilidad a la droga, origen bacteriano, número de bacterias inoculadas, pH del sustrato, viscosidad del agar, tiempo de incubación y actividad metabólica en contra del microorganismo (Silva et al, 2014). Motivo por el cual, en el presente trabajo no se evalua la "zona de inhibición", por ser un concepto tan amplio.…”
Section: Discussionunclassified
“…Our previous data have demonstrated that small molecules with a nitroimidazole pharmacophore (14) possess biological activities, with good antibacterial potency, against various infectious diseases (13). Antibiotics with nitrofuran (13, 15) also show inhibitory activities against oral bacteria such as S. mutans and E. faecalis (16)(17)(18). Here, we designed and synthesized compound ZY354, a hybrid of indolin-2-one and nitrofuran.…”
Section: Discussionmentioning
confidence: 99%
“…1), exhibited excellent bactericidal activity against both clinically related Gram-positive and Gramnegative bacteria, including methicillin-resistant Staphylococcus aureus (MRSA), methicillinsensitive Staphylococcus aureus (MSSA), Escherichia coli, and Pseudomonas aeruginosa (14). Antibiotics featuring nitrofuran, another antibacterial pharmacophore with a mode of action similar to that of nitroimidazole (13,15), have shown inhibitory activities against oral bacteria such as S. mutans and Enterococcus faecalis (16)(17)(18), indicating the good potential of this motif in the treatment of oral diseases such as dental caries. Hence, we combined indole-2-one and nitrofuran motifs to get a potent pharmacophore against oral bacteria ( Fig.…”
mentioning
confidence: 99%
“…Different small molecular antibiotics from natural products and synthetic compounds have been identified against S. mutans . Drug-repositioning is a commonly used approach to the identification of antimicrobial agents that inhibit S. mutan s. Nitrofuran, with a mode of action similar to that of nitroimidazole, shows inhibitory activity on oral bacteria such a s S. mutans and Enterococcus faecalis ( Silva et al., 2014 ; Ang et al., 2017 ). Based on the antimicrobial activity of nitrofuran, our group synthesized and identified a compound named ZY354, a water-soluble hybrid of indolin-2-one and nitrofuran, which showed potent antimicrobial activity and selectivity against S. mutans compared with CHX ( Zhang et al., 2019 ).…”
Section: Small Molecules That Inhibit Keystone Bacteria Associated Wi...mentioning
confidence: 99%